Analisis Data Panel Pengaruh Indeks Pembangunan Manusia dan Produk Domestik Regional Bruto terhadap Kemiskinan di Kabupaten atau Kota Provinsi Jawa Tengah Tahun 2011 – 2015 - Stevani Siburian; Fildzah Aptanta Henanda Sari (Nomicpedia: Journal of Economics and Business Innovation, 2022)
This writing is structured to determine the influence that exists on HDI and GRDP on poverty in 35 districts/cities in Central Java Province for the period 2011 – 2015. The sampling technique used in this paper is purposive sampling with secondary data types obtained from the official website of the Indonesian National Agency for Research. Center for Statistics. The data analysis technique used is panel data regression analysis using the Common Effects Model (CEM), Fixed Effects Model (FEM), and Random Effects Model (REM). The results of the analysis show that the panel data regression model that fits the data collection is the Random Effects Model (REM) with HDI and GRDP having a significant effect on poverty in districts/cities of Central Java Province in 2011 - 2015.